Uji Efektivitas Ekstrak Mimba (Azadirachta indica A. Juss.) untuk Mengendalikan Hama Penggerek Daun pada Tanaman Podocarpus neriifolius - WIBAWA, I PUTU AGUS HENDRA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2019)
The effectiveness analysis of neem plant (Azadirachta indica A. Juss.) to control leaf borer on plant Podocarpus neriifolius Plant maintenance and development cannot be avoided from pests and diseases. Losses due to pest or disease attacks encourage patients to control various efforts. So far the pest and disease control efforts carried out are still based on synthetic pesticides. The use of various types of synthetic pesticides, on the other hand bring problems to the environment such as causing poisoning to humans, killing non-target organisms, secondary pest outbreaks, pest resistance, soil, water and air pollution. One alternative pest control that can be done is by organic pesticides. One of the plants reported to have the ability to control pests is the neem plant (Azadirachta indica). This study aims to determine the effectiveness of neem extract in controlling leaf borer caterpillar on Podocarpus neriifolius compared to vegetable pesticides Dane brand and synthetic pesticides. The results of the research conducted, it was found that the most effective dose of mimba extract was 80 g/liter. Both wet and dry extracts are equally effective in controlling pests. Control using dry leaf extract with dose of 80 g/liter is more effective than using the Dane brand pesticide in three times the dose.